An in vivo role for Rho kinase activation in the tumour vascular disrupting activity of combretastatin A‐4 3‐O‐phosphate. (November 2014) - Williams, L J; Mukherjee, D; Fisher, M; Reyes‐Aldasoro, C C; Akerman, S; Kanthou, C; Tozer, G M
<x xml:space="preserve">Abstract</x> Background and Purpose Combretastatin A‐4 3‐O‐phosphate (CA4P) is in clinical trial as a tumour vascular disrupting agent (VDA) but the cause of blood flow disruption is unclear. We tested the hypothesis that activation of Rho/Rho kinase (ROCK) is fundamental to the effects of this drug in vivo. Experimental Approach Mouse models of human colorectal carcinoma (SW1222 and LS174T) were used. Effects of the ROCK inhibitor, Y27632, alone or in combination with CA4P, on ROCK activity, vascular function, necrosis and immune cell infiltration in solid tumours were determined. Mean arterial BP (MABP) was measured to monitor systemic interactions and the vasodilator, hydralazine, was used to control for the hypotensive effects of Y27632. Key Results Y27632 caused a rapid drop in blood flow in SW1222 tumours, with recovery by around 3 h, which was paralleled by MABP changes. Y27632 pretreatment reduced CA4P‐induced ROCK activation and partially blocked CA4P‐induced tumour vascular effects, in both tumour types. Y27632 also partially inhibited CA4P‐induced tumour necrosis and was associated with reduced immune cell infiltration in SW1222 tumours. Hydralazine caused a similar hypotensive effect as Y27632 but had no protective effect against CA4P treatment. Conclusions and Implications These results demonstrate that ROCK activity is critical for full manifestation of the vascular activity of CA4P in vivo, providing the evidence for pharmacological intervention to enhance the anti‐tumour efficacy of CA4P and related VDAs.